The Use of Digital Tools in the Educational Process of Preschool Educational Institutions - Kozak, Liudmyla; Litichenko, Olena; Harashchenko, Larisa; Shynkar, Tetiana (Educological discourse, 2025)
The article examines the possibilities of using digital tools in the educational process of preschool institutions. It analyzes both foreign and Ukrainian scholarly sources concerning the application of digital technologies in preschool education. The study outlines key aspects of implementing digital tools in educational interactions with preschool children, particularly the use of digital devices (such as smartphones, tablets, computers, projectors, and interactive whiteboards) for teaching science, mathematics, reading and writing, as well as the use of digital services (including educational games and AR-based mobile applications). The importance of preparing educators to effectively integrate digital technologies into the educational process of preschool institutions is substantiated. The article also highlights the experience of future educators in applying digital tools during their practical training in preschool institutions. The authors explore the possibilities of creating educational content for children using augmented reality (AR) digital tools such as Blippbuilder, MyWebAR, and ZapWorks. An algorithm for developing AR-based projects is proposed, and the main stages of applying AR technology during the organization of an educational quest game are described. The results of the observation of children and the analysis of students’ projects confirmed the effectiveness of implementing game quests with AR elements in the educational process of preschool institutions, demonstrating their benefits in stimulating children’s cognitive activity and fostering digital competence. The study concludes that the use of digital tools in preschool education practice is a powerful instrument of the educator’s personal and professional development. It contributes to the improvement of the quality of the educational process in preschool institutions, engaging children in active learning, and increasing both their motivation to study and their level of assimilation of educational material.